Microdeletions at 19p13.11p12 in five individuals with neurodevelopmental delay - Rieger, Melissa; Moutton, Sébastien; Verheyen, Sarah; Steindl, Katharina; Popp, Bernt; Leheup, Bruno; Bonnet, Céline; Oneda, Beatrice; Rauch, Anita; Reis, André; Krumbiegel, Mandy; Hüffmeier, Ulrike (European Journal of Medical Genetics, 2023)
Only few copy number variants at chromosome 19p13.11 have been reported, thus associated clinical information is scarce. Proximal to these copy number losses, we now identified deletions in five unrelated individuals with neurodevelopmental disorders. They presented with psychomotor delay as well as behavioral and sleeping disorders, while complex cardiovascular, skeletal, and various other malformations were more variable. Dysmorphic features were rather unspecific and not considered as a recognizable gestalt. Neither of the analyzed parents carried their offsprings' deletions, indicating de novo occurrence. The deletion sizes ranged between 0.7 and 5.2 Mb, were located between 18 and 24 megabases from the telomere, and contained a variable number of protein-coding genes (n = 25–68). Although not all microdeletions shared a common region, the smallest common overlap of some of the deletions provided interesting insights in the chromosomal region 19p13.11p12. Diligent literature review using OMIM and Pubmed did not identify a satisfying candidate gene for neurodevelopmental disorders. In the literature, a de novo in-frame deletion in MAU2 was considered pathogenic in an individual with Cornelia de Lange syndrome. Therefore, the clinical differential diagnosis of this latter syndrome in one individual and the encompassment of MAU2 in three individuals' deletions suggest clinical and genetic overlap with this specific syndrome. Three of the four here reported individuals with deletion encompassing GDF1 had different congenital heart defects, suggesting that this gene's haploinsufficiency might contribute to the cardiovascular phenotype, however, with reduced penetrance. Our findings indicate an association of microdeletions at 19p13.11/ 19p13.11p12 with neurodevelopmental disorders, variable symptoms, and malformations, and delineate the phenotypic spectrum of deletions within this genomic region.
CRIS-Team Scopus Importer:2022-12-16
Keywords: 19p13.11p12; Deletion; GDF1; Malformation; MAU2; NDD